1989
DOI: 10.1128/aac.33.3.316
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of intramuscular amopyroquin in healthy subjects and determination of a therapeutic regimen for Plasmodium falciparum malaria

Abstract: The disposition of amopyroquin was investigated in 10 healthy volunteers after a single 2-mg/kg (body weight) intramuscular dose of amopyroquin base. The major form of the drug in plasma and in whole blood was nonmetabolized amopyroquin, and only very low levels of its primary amine derivative were detected. After a rapid absorption phase (15 min), levels in plasma declined, following a tri-exponential model with a terminal elimination half-life of 129.6 + 92.5 h. The apparent volume of distribution (V/F) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

1990
1990
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 18 publications
1
12
0
Order By: Relevance
“…Terminal t1/2 were 14.5 hr, 22 hr and 5 days, respectively (Pussard et al, 1988;Verdier et al, 1989), indicating a correlation between the size of the animal and this parameter.…”
Section: The Pharmacokinetics Of Chloroquine In Mice : Implications Fmentioning
confidence: 99%
“…Terminal t1/2 were 14.5 hr, 22 hr and 5 days, respectively (Pussard et al, 1988;Verdier et al, 1989), indicating a correlation between the size of the animal and this parameter.…”
Section: The Pharmacokinetics Of Chloroquine In Mice : Implications Fmentioning
confidence: 99%
“…The persistence or reappearance of parasites in blood was always associated with a lower hematocrit value, which mainly reflected the level of parasitemia, as confirmed by the difference in hematocrit values (on day 7) of the children who succeeded or failed therapy. Among the patients, who failed therapy, however, those who were parasitemic on day The levels of ApQ in blood obtained with the regimen described here 24 h after the second injection were lower than the theoretic value predicted by concentration-time curve models obtained from Caucasian, adult, and healthy volunteers (16). Ethnicity, age, and disease-related factors may contribute to these differences.…”
Section: Materuils and Methodsmentioning
confidence: 62%
“…At the same time, multicenter studies in patients with acute malaria showed a poor efficacy when 3 mg/kg was used (16% in Gabon [n = 79]; 25% in Madagascar [n = 12]) and when 6 mg/kg was used (42% in Gabon [n = 25]) and only partial efficacy when 6 and 3 mg/kg were used at a 24-h interval (83% in Gabon [n = 23]; 80% in Cameroon [n = 78]) (10). From the results of those clinical trials and the results of a kinetic study in healthy subjects (16), we proposed the following regimen as being potentially therapeutic: two intramuscular injections of 6 mg/kg each at a 24-h interval.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…More excitingly, we developed a series of analogs where 4 ′ -hydroxy group was replaced by various amino substituents 4 (Paunescu et al , 2008 ). Furthermore, as AQ-analogs obtained by the replacement of the N -diethylamino function of the side chain, with a pyrrolidine cycle (amopyroquine, ApQ) or a Ntert -butyl group were proved to be as active and metabolically less labile (Hawley et al , 1996 ;Verdier et al , 1989 ), we completed our study with the development of parallel ApQ-analogs series. The substitution of 4 ′ -hydroxy by N -methylpiperazine (compound 5 ) or morpholine (compound 6 ) provided low nanomolar activity upon K1 chloroquino-resistant strain and low cytotoxicity (Paunescu et al , 2008 ).…”
Section: Introductionmentioning
confidence: 99%